Oral contraceptive use before first birth and risk of breast cancer: a case control study - Apter Dan; Pukkala Eero; Luostarinen Tapio; Hemminki Elina; Hakulinen Timo (BMC, 2002)
Abstract Background The aim of this study was first, to investigate whether women starting oral contraceptive (OC) use at a young age and before first birth have an increased risk for breast cancer and second, to report difficulties encountered in studying long-term health impacts of medical technologies. Methods Breast cancers occurring up until 1997 among 37153 Helsinki students born between 1946 and 1960 were identified by record linkage from the Finnish Cancer Registry; for each cancer case, five age-matched random controls were picked from the same student population. Those who had used the Helsinki Student Health Service (HSHS) at least three times (150 cases and 316 controls) form the final study subjects. Data on OC use and background characteristics were collected from patient records, and data on live births were derived from the population register. Odds ratios (OR) were adjusted for number of births, smoking and sports activity. Results Compared to the few non-users, OC users had a higher risk of breast cancer: the adjusted OR was 2.1 (95% confidence interval 1.1-4.2). Among OC users, no statistically significant differences in risk of breast cancer were found in regard to starting age or first birth, but small numbers made confidence intervals wide. Even though we had chosen students to be our study group, the population turned out to be unsuitable to answer our research question: most women had started their OC use old (at the age of 20 or later) and there were very few unexposed (almost all had used OC and before their first birth). Conclusions Because adoption of the modern pattern of OC use was not common among students, it is unlikely that the impact of early and extended OC use can be studied before 2010, when women born in the 1960s are 40 to 50 years old.